Ensuring women's safety: international legal aspect - Fomina, L. O. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2019)
In this article it was analyzed the provisions of the international legal acts for the right to security of the women; it was paid attention to the security measures; it was focused on the the existing problems in this area.